Sleep deprivation and NLRP3 inflammasome: Is there a causal relationship? - Amini, Mohammad; Yousefi, Zahra; Ghafori, Sayed Soran; Hassanzadeh, Gholamreza (Frontiers in Neuroscience, 2022)
In the modern era, sleep deprivation (SD) is one of the most common health problems that has a profound influence on an individual’s quality of life and overall health. Studies have identified the possibility that lack of sleep can stimulate inflammatory responses. NLRP3 inflammasome, a key component of the innate immune responses, initiates inflammatory responses by enhancing proinflammatory cytokine release and caspase-1-mediated pyroptosis. In this study, NLRP3 modification, its proinflammatory role, and potential targeted therapies were reviewed with regard to SD-induced outcomes. A growing body of evidence has showed the importance of the mechanistic connections between NLRP3 and the detrimental consequences of SD, but there is a need for more clinically relevant data. In animal research, (i) some animals show differential vulnerability to the effects of SD compared to humans. (ii) Additionally, the effects of sleep differ depending on the SD technique employed and the length of SD. Moreover, paying attention to the crosstalk of all the driving factors of NLRP3 inflammasome activation such as inflammatory responses, autonomic control, oxidative stress, and endothelial function is highly recommended. In conclusion, targeting NLRP3 inflammasome or its downstream pathways for therapy could be complicated due to the reciprocal and complex relationship of SD with NLRP3 inflammasome activation. However, additional research is required to support such a causal claim.